Epidemiological features and climatological effects on future malaria control in Indonesia - Rovik, Anwar; Rahayu, Ayu; Turnip, Oktaviani Naulita; Daniwijaya, Edwin Widyanto (Berita Kedokteran Masyarakat, 2025)
Purpose: Malaria is a leading cause of death worldwide, including in Indonesia. Climate change should be considered when addressing malaria control in Indonesia. This study examined the relationship between climatological parameters (temperature, wind speed, humidity, and rainfall) and malaria cases in Indonesia from 2006 to 2015. Methods: Data on climatological parameters were obtained from Indonesia's 2022 statistics, while malaria case data were taken from the annual report of Indonesia's Ministry of Health. Results were presented using maps, diagrams, and graphs. The associations between climatological parameters and malaria cases were analyzed annually using GraphPad Prism 9 software. Results: Between 2006 and 2015, the API fluctuated each year. Papua province had the highest malaria incidence in Indonesia (25.5%). A significant decline in malaria cases was observed outside Papua province, whereas cases in Papua tended to increase annually. During this period, annual temperature ranged from 23.39°C to 28.44°C, wind speed from 1.01 m/s to 17.54 m/s, relative humidity from 70.85% to 85.84%, and rainfall from 99.74 to 3,838.2 mm3. Conclusion: From 2006 to 2015, annual temperature, rainfall, and relative humidity showed weak positive correlations with the API, whereas annual wind speed showed a negative correlation.